Bruce L. Keenan, Book of Ordinances of the City of Wichita 45 (1900) - (:unkn) unknown (My University, 1899)
§ 1: That any person, not an officer of the law in the execution of his duty, who shall in the city of Wichita, draw a pistol, revolver, knife, or any other deadly weapon upon another person shall upon conviction, be fined not less than twenty-five dollars nor more than one hundred dollars.
Keywords: BRANDISHING